Design of 6E-Instructional Model Assisted by GeoGebra Media in Improving Students' Mathematical Visual Spatial Ability on the Topic of Prism - Natan Prasetya; Maximus Gorky Sembiring; Sudirman Sudirman (Pendidikan Matematika STKIP Kusuma Negara, 2025)
Students’ mathematical visual-spatial ability is crucial for understanding geometry. However, its suboptimal level calls for quality learning. The purpose of this study was to test the quality of the Geogebra-assisted 6E-Instructional Model (6E-IM) on students' spatial visual ability; test the effect of Geogebra-assisted 6E-IM on spatial visual ability; and describe students' spatial visual ability after receiving the Geogebra-assisted 6E-IM model. This study used an embedded design. The Geogebra-assisted 6E-IM model (independent variable) was measured through interviews, while spatial visual ability (dependent variable) was assessed using questionnaires. The results showed that the geometry learning instrument with the 6E-IM learning model assisted by Geogebra was in the very good category with a score of 92%, and positively affected students' visual-spatial abilities. Description of students' spatial visual ability involving 2 students in each category, in the high category, met all indicators of spatial visual ability; students with moderate spatial visual ability met two indicators of spatial visual ability; and students with low spatial visual ability met one indicator of spatial visual ability. The results of this study are expected to be Geogebra integrated 6E-IM Design can be used by teachers to improve students' visual spatial abilities.